Features of the management of cancer patients during the COVID-19 pandemic - M. I. Sekacheva; A. S. Rusanov; A. S. Fatyanova; A. M. Boroda; A. L. Istranov; S. N. Rusanov; Yu. V. Babayeva; E. V. Poddubskaya (Сеченовский вестник)
Novel coronavirus infection, causing COVID-19, is not fully controlled for today. In periodicals, there are often reports of a high risk of severe complications in cancer patients during the development of COVID-19. The review presents information from literary sources based on the experience gained in overcoming this formidable disease and its consequences using the examples of foreign colleagues of clinicians, as well as domestic experience and recommendations for the treatment of cancer during the pandemic COVID-19 of the National Medical Research Center for Radiology of the Ministry of Health of Russia with the participation and support of the Association of Oncologists of Russia and the Association of Health Organizers in Oncology. The information is based on actual data collected through the search of sources in abstract and sciencemetric electronic databases, open access resources in Russian and English. The review presents recommendations from international and domestic professional communities regarding the routing and multidisciplinary treatment of cancer patients during the pandemic period.